Структурно-аналитическая интерпретация сигналов в системах фазового управления вентильных преобразователей - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The structural image of the passage of signals in phase control systems by means of valve transformers is proposed. The mathematical description of processes in these systems is realized on the basis of a special expansion of step functions.